Uma experiência política na Casa-museu: as trajetórias da política cultural empreendida no espaço cultural Casa das Onze Janelas em Belém-Pará (1998-2018) - SAMPAIO, Lívia Morbach Condurú Gurjão (Universidade Federal do Pará, 2018)
Created in 1998 by the State Government of Pará, the Espaço Cultural das Casa das Onze Janelas, opened to the public in December 2002, becoming an important public museum of contemporary Brazilian art, based in the northern portion of the country, specifically in Belém, Pará. Through Decree no. 1,568 of June 17, 2016, signed by the then governor Simão Jatene (PSDB), the same political group that created the museum defenestrates it from its original historical building, Casa das Onze Janelas, thus starting a long battle between civil society and the State Government. This qualitative research constitutes a cartography capable of demonstrating a political experience of the Casa-body as Espaço Cultural Casa das Onze Janelas from its conception, first as an idea in 1998, making it possible to detail the struggle between different forces that composed its trajectory of resistance. Power clash between the State Government of Pará and the State's visual arts system for the maintenance of the Casa as a museum of Brazilian contemporary art, regarding not only the destabilization of the State's goal of transforming the Casa into one of the headquarters of the Gastronomic Pole of the Amazon; but also regarding the conditions that allowed for its diversified schedule and expansion of its collection throughout much of the Casa-museum's history, largely neglected by the absence of a state cultural policy that would support its multiple needs. In carrying out this cartography, the Schyzoanalytical methodology was applied, made possible by the agency of several intercessors, supported by semi-structured interviews with nine players of the visual arts system, directly linked to the Espaço Cultural Casa das Onze Janelas; my own trajectory as a cultural producer; the examination of official documents; the collection of interviews, conducted by local media, with Paulo Chaves Fernandes; and bibliographic review. By experiencing this cartography, it has become clear that the cultural policy undertaken for most of the artistic languages that shape the cultural capital of Pará by the PSDB since 1995, instead of contributing to the socioeconomic balance of the communities that make up the State, accentuate its inequalities. State apparatus interested only in keeping its pacts and alliances with the mercantile power fixed; and the unilateral interests of those who govern us.